Quadratic Displacement Maps for Heightmap Rendering - Kiglics, Mátyás; Valasek, Gábor; Bálint, Csaba; Bán, Róbert (Acta Cybernetica, 2024)
We present a higher-order representation of heightfields by constructing unbounding revolved parabolas about every texel of the height texture. These surfaces of revolution do not intersect the interior of the volume defined by the heightfield. We present a simple generation algorithm and show that these maps can be rendered by computing intersections between lines and parabolas in the plane. We compare its quality and performance with cone step mapping.